An Examination of Attitudes toward Bisexual People at the Intersections of Gender and Race/Ethnicity. Issue 4 (14th November 2022) - Feinstein, Brian A.; Benjamin, Isabel; Dorrell, Kate D.; Foley, Sydni E.; Blumenau, Helena S.; Cragun, Ryan T.; Manalastas, Eric Julian
Abstract: People report more negative attitudes toward bisexual than gay/lesbian individuals, but little is known about attitudes at the intersections of gender and race/ethnicity. We examined whether attitudes toward bisexual people differed depending on: 1) target gender identity (man, woman), gender modality (cisgender, transgender), and race/ethnicity (White, Black, Hispanic); and 2) participant gender identity (man, woman) and race/ethnicity (White, person of color). As part of a cross-sectional survey, 552 participants rated their feelings toward 12 bisexual targets who varied in gender identity/modality and race/ethnicity. A repeated-measures ANOVA indicated that participants rated bisexual men more negatively than bisexual women, transgender bisexual individuals more negatively than cisgender bisexual individuals, and Black/Hispanic bisexual individuals more negatively than White bisexual individuals. However, differences based on target gender identity and race/ethnicity were only observed for cisgender targets, and most effects were only observed for male participants. Efforts to improve attitudes toward bisexual people must account for heterogeneity based on target/participant characteristics.